5-Hydroxymethyl-2-furfural, a clinical trials agent for sickle cell anemia, and its mono/di-glucosides from classically processed steamed Rehmanniae Radix - Lin, An-Shen; Qian, Keduo; Usami, Yoshihide; Lin, Li; Itokawa, Hideji; Hsu, Charleson; Morris-Natschke, Susan L.; Lee, Kuo-Hsiung (Journal of natural medicines, 2008)
Rehmanniae Radix (Di Huang) is one of the most important traditional Chinese medicines (TCM), and is used for multiple therapeutic purposes. In our investigation of the chemical constituents of Rehmanniae Radix, steamed roots were prepared by the classical processing method. Reversed-phase HPLC of the 50% MeOH extract of steamed Rehmanniae Radix yielded three 5-hydroxymethylfurfural derivatives. The new furfural disaccharide 5-(α- d -glucopyranosyl-(1→6)-α- d -glucopyranosyloxymethyl)-2-furancarboxaldehyde ( 1 ) was isolated and characterized, together with its known aglycone 5-hydroxymethyl-2-furfural ( 3 ), which is currently in sickle cell anemia Phase I clinical trials, and its corresponding monosaccharide 5-(α- d -glucopyranosyloxymethyl)-2-furancarboxaldehyde ( 2 ), which was isolated as a natural product for the first time. The presence of these three compounds, particularly 3 , which were not found in the unprocessed extract of Rehmanniae Radix, could substantiate the traditional medicinal use of steamed Rehmanniae Radix.